The Selective Serotonin 2A Receptor Antagonist Sarpogrelate Prevents Cardiac Hypertrophy and Systolic Dysfunction via Inhibition of the ERK1/2–GATA4 Signaling Pathway - Kana Shimizu; Yoichi Sunagawa; Masafumi Funamoto; Hiroki Honda; Yasufumi Katanasaka; Noriyuki Murai; Yuto Kawase; Yuta Hirako; Takahiro Katagiri; Harumi Yabe; Satoshi Shimizu; Nurmila Sari; et al. (Pharmaceuticals, 2021)
Drug repositioning has recently emerged as a strategy for developing new treatments at low cost. In this study, we used a library of approved drugs to screen for compounds that suppress cardiomyocyte hypertrophy. We identified the antiplatelet drug sarpogrelate, a selective serotonin-2A (5-HT2A) receptor antagonist, and investigated the drug’s anti-hypertrophic effect in cultured cardiomyocytes and its effect on heart failure in vivo. Primary cultured cardiomyocytes pretreated with sarpogrelate were stimulated with angiotensin II, endothelin-1, or phenylephrine. Immunofluorescence staining showed that sarpogrelate suppressed the cardiomyocyte hypertrophy induced by each of the stimuli. Western blotting analysis revealed that 5-HT2A receptor level was not changed by phenylephrine, and that sarpogrelate suppressed phenylephrine-induced phosphorylation of ERK1/2 and GATA4. C57BL/6J male mice were subjected to transverse aortic constriction (TAC) surgery followed by daily oral administration of sarpogrelate for 8 weeks. Echocardiography showed that 5 mg/kg of sarpogrelate suppressed TAC-induced cardiac hypertrophy and systolic dysfunction. Western blotting revealed that sarpogrelate suppressed TAC-induced phosphorylation of ERK1/2 and GATA4. These results indicate that sarpogrelate suppresses the development of heart failure and that it does so at least in part by inhibiting the ERK1/2–GATA4 signaling pathway.